Analysis of thermal-regulation and comfort associated with user perceptions and garment performance - Collins, P. K.; Purdie, R.; Hinck, K.; Leissner, C.; Scicchitano, B.; Gathercole, R.; Usma, C. (Proceedings, 2018)
This study is designed to understand post-exercise comfort perceptions by exploring the relationship between users and garments. Influenced by new technologies from fibres, manufacturing techniques, and surface coatings athletic apparel is changing. These technologies can influence the quality of daily pursuits, and by assessing psychological and physiological responses to physical activity, it`s possible to optimise garment performance. To that end, this paper presents a qualitative and quantitative analysis of thermal regulation and comfort perceptions within a controlled laboratory environment. A group of eleven healthy athletic female participants performed a twenty-minute high-intensity interval training running session (HIIT) and subsequent transition activity period. Participants had vitals monitored and were periodically prompted with specific questions to gauge their perceptions of effort, temperature, exertion, and comfort. The results suggest that perceptual differences are minor when evaluating apparel design during high-intensity exercise, and perhaps the efforts of garment design optimization would be best placed in an immediately subsequent activity type.